Temperature differently affected methanogenic pathways and microbial communities in sub-Antarctic freshwater ecosystems - Lavergne, Céline; Aguilar-Muñoz, Polette; Calle, Natalia; Thalasso, Frédéric; Astorga-España, Maria Soledad; Sepulveda-Jauregui, Armando; Martinez-Cruz, Karla; Gandois, Laure; Mansilla, Andrés; Chamy, Rolando; Barret, Maialen; Cabrol, Léa (Environment International, 2021)
International audience